Should Revision Trainees Think Aloud while Revising Somebody Else’s Translation? Insights from an Empirical Study with Professionals - Robert, Isabelle; Brunette, Louise (Meta, 2016)
This paper reported on a follow-up study whose aim was fourfold: 1) to determine which variables do seem to influence the amount of verbalization of professional revisers when they verbalize their thoughts while revising somebody else’s translation, 2) to determine what kind of revision sub-processes are verbalized, 3) to determine the relation between the type of verbalizations and revision product and process, and 4) to draw conclusions for revision didactics. Results show that variables that could have influenced the verbalization ratio of revisers had no effect on that ratio, except the revision experience. As far as verbalized subprocesses are concerned, it appeared that revisers rarely verbalized a maxim-based diagnosis, but that the more they verbalized such a problem representation, the better they detected, the better they revised, but the longer they worked. Results also show that participants who verbalized a problem representation together with a problemsolving strategy or a solution, detected better, but worked longer. Further research could focus on a particular subcompetence of the revision competence: the ability to explain.